SYNTHESIS AND CHARACTERISTICS OF CHITOSAN FROM WASTE FISH SCALES AND CRAB SHELLS PRODUCED IN KUPANG CITY - Sisiliana Mbiking Kelen; Maria Oktaviani Hartini; Metriana Fahik; Luthfiah Usman; Nur R. Adawiyah Mahmud (Jurnal Perikanan Unram, 2024)
Fish scales are the result of fishing activities that are simply thrown away. Fish scales that are thrown away can become waste which has a negative impact on the environment. Crab shells are a problem that needs to be solved. One use of crab shell waste is processing it into chitosan. The aim of this research is to find out how to make chitosan from waste fish scales and crab shells, calculate the yield and water content, and then the method used to make chitosan from waste fish scales and crab shells including the stages of deproteinization, demineralization, and deacetylation. The differences in chitosan synthesis from waste fish scales and crab shells mainly depend on the extraction time, temperature, and concentration of NaOH and differences in the texture of the waste samples used. The results obtained are chitosan from fish scales and crab shells. Chitosan was obtained from waste fish scales (25.33-29.33%) and chitosan from crab shells (50%). From the research carried out it can be concluded that waste fish scales and crab shells can be converted into chitosan, the FT-IR results of chitosan from fish scales, crab shells, and commercial have different results, crab shell chitosan has better FT-IR results than commercial chitosan and fish scales.